Financialization relational approaches - Hann, C. M., 1953-; Kalb, Don, 1959- (Max Planck studies in anthropology and economy ;, 2020)
"Beginning with an original historical vision of financialization in human history, this volume then continues with a rich set of contemporary ethnographic case studies from Europe, Asia and Africa. Authors explore the ways in which finance inserts itself into relationships of class and kinship, how it adapts to non-Western religious traditions, and how it reconfigures legal and ecological dimensions of social organization, and urban social relations in general. Central themes include the indebtedness of individuals and households, the impact of digital technologies, the struggle for housing, financial education, and political contestation"--